(untitled) (UNIZIK Journal of STM Education, 2025)
The purpose of the study was to ascertain if self-motivation is a predictor of secondary school students’ academic achievement in Biology in Anambra State. One research question gave direction to the study while one hypothesis was tested at the 0.05 level of significance. A correlational research design was employed for the study. The population of this study was made up of 20, 138 biology senior secondary SS2 students in the 266 public secondary schools in Anambra State. The sample for the study comprised 840 SS 2 students for the 2024/2025 academic session drawn through a multi-stage sampling procedure. Face-validated Self-Motivation Questionnaire (SMQ) was used to collect data. The data collected were analyzed using multiple regression. The findings of the study revealed that self-motivation positively and insignificantly predicted secondary school students’ academic achievement in biology. Based on the findings of the study, it was recommended that Biology teachers should encourage students to be self motivated to improve their academic achievement in Biology.